Factors that affect scientific publication in Africa—A gender perspective - Beaudry, Catherine; Prozesky, Heidi; St-Pierre, Carl; Mirnezami, Seyed Reza (Frontiers in Research Metrics and Analytics, 2023)
A large body of literature on gender differences in scientific publication output has clearly established that women scientists publish less that men do. Yet, no single explanation or group of explanations satisfactorily accounts for this difference, which has been called the “productivity puzzle”. To provide a more refined portrait of the scientific publication output of women in relation to that of their male peers, we conducted a web-based survey in 2016 of individual researchers across all African countries, except Libya. The resulting 6,875 valid questionnaires submitted by respondents in the STEM, Health Science and SSH fields were analyzed using multivariate regressions on the self-reported number of articles published in the preceding 3 years. Controlling for a variety of variables including career stage, workload, mobility, research field, and collaboration, we measured the direct and moderating effect of gender on scientific production of African researchers. Our results show that, while women's scientific publication output is positively affected by collaboration and age (impediments to women's scientific output decrease later in their careers), it is negatively impacted by care-work and household chores, limited mobility, and teaching hours. Women are as prolific when they devote the same hours to other academic tasks and raise the same amount of research funding as their male colleagues. Our results lead us to argue that the standard academic career model, relying on continuous publications and regular promotions, assumes a masculine life cycle that reinforces the general perception that women with discontinuous careers are less productive than their male colleagues, and systematically disadvantages women. We conclude that the solution resides beyond women's empowerment, i.e., in the broader institutions of education and the family, which have an important role to play in fostering men's equal contribution to household chores and care-work.